Review of the application of ε‐poly‐L‐lysine in improving food quality and preservation. Issue 10 (14th August 2019) - Tuersuntuoheti, Tuohetisayipu; Wang, Zhenhua; Wang, Ziyuan; Liang, Shan; Li, Xinping; Zhang, Min
Abstract: ε‐poly‐L‐lysine (ε‐PL) is a cationic polypeptide. As a natural antibacterial peptide, it has attracted much attention in the food, biomedical, and chemical industries because of its wide antibacterial spectrum and safety. Use of ε‐PL in the food industry is common, due to its biological activity and functional properties. This paper focuses on the physiochemical properties, safety, antibacterial activity, antibacterial mechanism of action, and applications of ε‐PL in improving the quality and shelf life of various foods. Practical applications: As green consumerism is becoming more popular, there is a growing demand for natural preservatives. This work provides basic theories and methods for the application of ε‐PL in food preservation. This paper gives scientific guidelines for consumers and producers of agricultural products. Thus, it may promote the utilization of ε‐PL in the food industry and reduce the use of chemical preservatives.